2011
DOI: 10.1007/s11661-011-0935-1
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Decomposition of Ferrite in a High-Nitrogen, Nickel-Free Duplex Stainless Steel

Abstract: The formation and crystallography of second phases during isothermal decomposition of ferrite (a) in a high-nitrogen, nickel-free duplex stainless steel was examined by means of transmission electron microscopy (TEM). At an early stage of aging, the decomposition of a started along the a/c phase boundaries where sigma (r) phase and secondary austenite (c 2 ) precipitated in the form of an alternating lamellar structure. The combined analyses based on the simulation of diffraction patterns and stereographic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The morphology of the CrN-Cr 2 N clusters was further analyzed with respect to the orientations within individual clusters measured by TKD (see Figure 5). An OR was identified between CrN and Cr 2 N matching the fcc-Cr 2 N OR reported for high-nitrogen austenitic stainless steels, [24] in this case ð111Þ CrN jjð0001Þ Cr 2 N and ½ 110 CrN jj½ 1100 Cr 2 N (see Figure 8(b)). This is reasonable due to the close resemblance of cubic halite-type crystal structure of CrN and the fcc structure of austenite.…”
Section: Chromium Nitride Formationsupporting
confidence: 79%
“…The morphology of the CrN-Cr 2 N clusters was further analyzed with respect to the orientations within individual clusters measured by TKD (see Figure 5). An OR was identified between CrN and Cr 2 N matching the fcc-Cr 2 N OR reported for high-nitrogen austenitic stainless steels, [24] in this case ð111Þ CrN jjð0001Þ Cr 2 N and ½ 110 CrN jj½ 1100 Cr 2 N (see Figure 8(b)). This is reasonable due to the close resemblance of cubic halite-type crystal structure of CrN and the fcc structure of austenite.…”
Section: Chromium Nitride Formationsupporting
confidence: 79%
“…It has been shown that the mechanism of σ-phase precipitation is a co-precipitation transition of α phase: α→σ + γ 2 [ 15 , 23 , 24 , 25 ]. The diffusion rate of alloy elements in the α phase is relatively high.…”
Section: Resultsmentioning
confidence: 99%
“…Alloying N is frequently adopted for DSSs because of its advantages in performance improvement [25,[30][31][32][33][34]. Thus, commercial DSSs including UNS S32101, UNS S32304, UNS S32205, and UNS S32750, contain 0.1-0.3 wt% N. However, alloying C to DSSs has rarely been attempted, although C is found to be beneficial to performances of γ-SSs, similarly to N. Generally, C content was carefully controlled to be less than 0.03 wt% for commercial DSSs, because DSSs can provide more sites to Cr 23 C 6 precipitations such as phase boundaries than the γ-SS [19,35,36].…”
Section: Introductionmentioning
confidence: 99%